Consumer Protection Law in Indonesia: Legal Framework, Enforcement, and Challenges - Irawan1, Donny; Utami, Rahayu Sri; Idhom, Idhom; Darmanto, Moch Oka Syah Darmanto (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: This study analyzes the legal framework, enforcement, and contemporary challenges of consumer protection law in Indonesia, focusing on Law No. 8 of 1999 (the Indonesian Consumer Protection Law) in the digital economy era. Methodology/approach: Normative juridical research using a literature review and comparative analysis of legislation, court decisions, and scholarly articles. Tools include Mendeley for reference management and Turnitin (no repository) for plagiarism checks. Results/Findings: This study finds that Indonesia has a strong normative consumer protection framework; however, enforcement is fragmented. Digital transactions, fintech, and e-commerce create risks that are not fully addressed by existing laws. Weak institutional coordination and low consumer awareness limit effective protection, causing many violations to remain unresolved. Conclusions: This study concludes that Indonesia’s consumer protection framework is normatively strong but faces challenges in the digital economy. The emerging risks from e-commerce and fintech have not been fully addressed, while fragmented enforcement, weak institutional coordination, and low consumer awareness limit their effectiveness. Therefore, improvements in regulatory adaptation, institutional integration, and legal literacy are required to ensure better consumer protection. Limitations: This study is limited to a normative legal analysis based on the literature and statutory review. It does not include empirical field surveys, interviews, or primary data from consumers, regulators, or business actors. Contributions: Provides updated insights for regulators, academics, and practitioners on improving consumer protection in the digital economy.